RESTORASI MEIJI : AWAL KEBANGKITAN NEGARA JEPANG - , DYAH SINTA PUSPA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Japan has a lot of interesting history and culture. This is one of the reasons why the writer likes Japanese history. The selected theme of this final assignment is Meiji Restoration: The Beginning of Japanese Resurgence. In this final assignment, the writer describes the social life of Japanese people in three aspect